Effects of Electroacupuncture at Baihui and Shenting Acupoints on Learning and Memory and Synaptic Plasticity in Rats with Cerebral Ischemia-reperfusion Injury - Xiaomin LIN; Jia HUANG; Xiaofang YOU; Bingbing LIN; Lidian CHEN (康复学报)
Objective:To observe the efficacy of electroacupuncture at Baihui (DU20) and Shenting (DU24) acupoints on learning and memory and synaptic plasticity in rats after cerebral ischemia/reperfusion (I/R) injury.Methods:Thirty-six male Sprague-Dawley rats were randomly divided into the sham group, the ischemia/reperfusion (I/R) group and the electroacupuncture group after surgery. Twenty-four rats were performed the focal cerebral ischemia and reperfusion injury on the left middle cerebral artery by suture method for 2 hours and another 12 rats were subjected to separation of vessels. The 24 rats were modeled with middle cerebral artery occlusion (MCAO) for 2 hours and then reperfusion. The rats of electroacupuncture group received electroacupuncture at Shenting and Baihui acupoints once a day for 7 days. Rats in another 2 groups were only grabbed under the same condition without intervention. Learning and memory ability were tested by Morris water maze. The maze was started at 3th and lasted for 5 days. The changes of synaptic ultrastructure in the hippocampus were observed by transmission electron microscope. Immunohistochemistry was used to test the expression of postsynaptic density protein 95 (PSD-95) and synaptophysin (SYN) in the hippocampus.Results:Compared with the I/R group, the latency of water maze decreased and the times crossing the platform increased in the sham group (P<0.001) and the electroacupuncture group (P<0.01). Trajectory crossing platform on the 5th day focused on the platform while the trajectory-crossing platform in the I/R group was irregular. The structure of the hippocampus CA1 area of the electroacupuncture group was more clear and complete. And compared with the I/R group, the sham group and the electroacupuncture group increased the expression of PSD-95 in hippocampus (P<0.001). Compared with the I/R group, the expression of SYN in hippocampus increased in the sham group (P<0.001) and the electroacupuncture group (P<0.01).Conclusion:Electroacupuncture can improve learning and memory ability in rats. The mechanism may be related to the improvement of synaptic plasticity and the increase of the expression of PSD-95 and SYN.